Measurement of air drag as physics experiment enrichment at senior high school laboratory using the air track apparatus - Listiaji, Prasetyo; Taufiq, Muhamad; Tirtasari, Ni Luh; Kholidah, Anisia; Tanjung, Nia Annisa Ferani (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
Linear air track is often used in physics learning for linear motion experiments because it can reduce friction between objects with trajectories. However, the use of air tracks for motion experiments in schools often does not care about aspects of air drag, so the purpose of this study is to calculate the air friction contained in the air track and as an offer of enrichment experiments at senior high school. The research method used is an experimental method that uses a set of air track experimental devices consisting of trajectors, carts, blower, and time counters with light sensors. Cart objects with a mass of 120.02 gram is given the initial velocity variation 12.272 cm/s, 16.286 cm/s and 24.599 cm/s. Then the time recorded when the cart crosses the distance of 10 cm to 110 cm at intervals of 10 cm. This experiment is conducted in the Integrated Science Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang. The second Newton law has been derived to obtain a special exponential function, so the relation between distance and time is obtained. The non-linear relation between distance and time shows the effect of air drag. Then, fitting the graph of the distance and time relation so that the air drag constants obtained are (10.6 ± 0.1) gram/s, (10.6 ± 0.2) gram/s, and (11.1 ± 0.2) gram/s. The results of the air drag constants obtained can be additional data as a factor affecting experiments using linear air track and can be enrichment experiments at senior high school laboratory.